First report of Mycoplasma leachii isolation associated with disease in dairy calves in Argentina = Primer aislamiento de Mycoplasma leachii asociado a enfermedad en terneros de tambo en Argentina - Neder, Veronica Elizabeth (2018)
There are few reports about the isolation of Mycoplasma species associated with cattle disease in Argentina. In this work we describe the detection of Mycoplasma leachii associated with disease in dairy calves in Santa Fe Province, Argentina. Samples obtained from a 4 day-old dairy calf suffering from polyarthritis and from two other calves, one with arthritis and the other one with a mandibular abscess, were subjected to microbiological culture. Classical culture and generic PCR confirmed the presence of Mycoplasma spp. The spacer region between the 16S and 23S ribosomal RNA gene from the first isolate was amplified and sequenced. The sequence obtained showed 99% identity with M. leachii. A PCR was developed to amplify a specific fragment of the 16S-23S ITS region corresponding to M. leachii, which allowed to identify the isolates associated with disease in calves.